2020
DOI: 10.3390/agronomy10040608
|View full text |Cite
|
Sign up to set email alerts
|

High Soybean Yield and Drought Adaptation Being Associated with Canopy Architecture, Water Uptake, and Root Traits

Abstract: Water stress is the main abiotic factor that limits soybean grain yield. We investigated eight soybean cultivars under well-watered (WW) and terminal drought stress (TDS) conditions to determine the traits associated with water saving and the relationship between water use, root morphology, canopy architecture, flower and tagged-pod number, and yield performance. Under WW conditions, the average grain yield across the new soybean cultivars was significantly higher (18.7 g plant−1 vs. 15.1 g plant−1), but signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
1
14
2
1
Order By: Relevance
“…Merlin is slightly older than SG Anser or Abelina. Many studies have confirmed that older cultivars find it more difficult to adjust to environmental conditions and stress-related factors, which results in their poorer growth and yield performance [53][54][55][56]. In the present work, the mean nitrogen content in seeds, roots and post-harvest residues was around 45, 11.0 and 5.5 g•kg −1 , respectively.…”
Section: Discussionsupporting
confidence: 66%
“…Merlin is slightly older than SG Anser or Abelina. Many studies have confirmed that older cultivars find it more difficult to adjust to environmental conditions and stress-related factors, which results in their poorer growth and yield performance [53][54][55][56]. In the present work, the mean nitrogen content in seeds, roots and post-harvest residues was around 45, 11.0 and 5.5 g•kg −1 , respectively.…”
Section: Discussionsupporting
confidence: 66%
“…Each rhizobox was filled with 26 kg of soil-sand mix. Basal fertiliser (urea, triple superphosphate, and sulphate of potash), comprising 190 mg kg −1 N, 110 mg kg −1 P, and 130 mg kg −1 K dry soil, was mixed into the top 20 cm of soil in each rhizobox [33]. Each rhizobox received an equal amount of macro-and micro-nutrients from commercial liquid fertiliser (Thrive; Yates, Australia) on a % w/v basis, with N (11), P (2.5), K (8), Mg (0.5), Mo (0.005), Cu (0.043), B (0.13), Zn (0.34), Fe (0.34), S (0.53), and Mn (0.26) as a top-dressing four weeks after emergence to ensure proper plant growth and development.…”
Section: Plant Materials and Growing Conditionsmentioning
confidence: 99%
“…The root system seems to be strongly related with drought tolerance in legumes [31] and has been highlighted for its potential applicability in drought tolerance screenings in soybean (Glycine max L.) [36,37], chickpea (Cicer arietinum L.) [18,27,38], common bean (Phaseolus vulgaris L.) [39,40], faba bean (Vicia faba L.) [41] and lentil (Lens culinaris ssp. culinaris Medikus) [42].…”
Section: Root-related Parametersmentioning
confidence: 99%
“…In cowpea, root traits were suggested to have an important role in drought avoidance [12] but their use in drought tolerance screenings is still not commonly applied, as they might involve complicated procedures using specific chambers that often require access to recently developed imaging techniques and high-throughput phenotyping software that allow the visualization of the three dimensional distribution of the root in the soil [16,43]. Different legume crops present distinct responses to drought regarding root development: common bean [39], faba bean genotypes [41] and soybean [37], show a reduced root development, while, in chickpea genotypes [18,27,38] and in some species of the genus Vigna [15], root growth seems to be stimulated. Moreover, Iseki et al [15] verified that the genotypes' tolerance levels were different between terminal and non-terminal drought treatments.…”
Section: Root-related Parametersmentioning
confidence: 99%